The relationships between social internet use, social contact, and loneliness in older adults - Jeroen H.M. Janssen; Theo G. van Tilburg; Erik J. van Ingen; Rense Corten; Geeske Peeters; Marcel G.M. Olde Rikkert (Scientific Reports)
Abstract Social internet use might decrease loneliness, potentially by increasing social contact. Vice versa, loneliness might decrease social internet use by decreased social contact. However, few studies explored these associations longitudinally. This study aimed to assess the longitudinal, bidirectional associations between frequency of social internet use, loneliness, and social contact (measured as the number of frequently contacted personal network members). We used four waves of the Longitudinal Aging Study Amsterdam (2011-13, 2015-16, 2018-19, 2021-22) in a sample of 1923 Dutch older adults (age 55–98). We applied random intercept cross-lagged panel models to test the bidirectional and mediational relationships. We found a longitudinal association between social internet use and subsequent loneliness, β = -0.07, p = .008, but no evidence of mediation of social contact, nor of a reversed association. These results strengthen existing evidence for a positive association of social internet use in decreasing loneliness. In contrast, more loneliness did not predict a difference in social internet use, suggesting that this reversed relationship is more complex or dependent on individual characteristics.